Using Teaching Analytics to Reflect on the Teaching Design - Hachem Alaoui Harouni, Moulay; El-Kaber, El-Kaber; Ziti, Cherif (International Journal of Engineering and Technology, 2019)
Teaching is encouraged through the support and the collaboration of other teachers. Data mining comes as a way to better reflect on teaching design as well as classroom practices. In this paper we are going to use the concept of Teaching Analytics as a tool that can help teacher analyse their educational design and that enable them to create better learning conditions for their students in our platform. This article also includes a comparison of lesson plan between two teachers at the Shariaa University, Fez.Â